A longitudinal, quantitative study of student attitudes towards audio feedback for assessment. Issue 7 (3rd October 2017) - Parkes, Mitchell; Fletcher, Peter
Abstract: This paper reports on the findings of a three-year longitudinal study investigating the experiences of postgraduate level students who were provided with audio feedback for their assessment. Results indicated that students positively received audio feedback. Overall, students indicated a preference for audio feedback over written feedback. No statistically significant differences were found between male and female students' attitudes, suggesting that both sexes held similar attitudes towards audio feedback. Students also indicated a preference for audio feedback that was recorded simply and returned promptly over delayed, more sophisticatedly recorded and edited feedback.